Percutaneous absorption of UV filters contained in sunscreen cosmetic products - González, Zacarías León (Springer, 2014)
Zacarías León's thesis describes the development and validation of analytical methods to estimate the processes set in motion by percutaneous absorption of UV filters in sunscreen cosmetic products. León describes these methods in both in vitro and non-invasive in vivo methodologies. Currently dermatologists recommend the use of sunscreen products not only under conditions of extreme exposure to the sun but also in daily situations. However the chemical compounds in these products contain may lead to undesired processes and cause induced toxicity, estrogenic effects and endocrine activity. León establishes methods to investigate these effects and provides valuable information on the undesired side effects associated with the use of UV filters found in sunscreen products. The work in this thesis has led to a number of publications in renowned analytical chemistry journals